Influence of Horizontal Pipe Length to Flooding of Counter Current of Water-Air Flow in Complex Pipe - Hartono, Samuel; Deendarlianto, Deendarlianto (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2017)
This research has been conducted study the effect of horizontal pipe length on flooding phenomenon. Observation of the flow phenomenon has used high speed camera. Working fluids for this study were water-air and the water flow was countercurrent to the air through a hot leg simulator. Hot leg simulator consisted of an acrylic horizontal pipe with inside diameter of 25.4 mm and an elbow with inclination angle of 500. The ratio of length to diameter pipe used in this study L/D = 25, L/D = 50 and L/D = 94.5. Water superficial velocity (JL) were 0.016 m/s, 0.049 m/s, 0.082 m/s. For each water superficial velocity, air superficial velocity (JG) was increased gradually with 0.1646 m/s from 0 m/s until flooding phenomenon appeared. Time interval to change air superficial velocity was 15 seconds. The result of this study was flooding phenomenon appeared earlier for higher L/D, and it was observed that the onset of flooding shifted toward the bend. It was also observed that flooding phenomenon shifted away from the bend for higher JL while L/D kept constant.